Peningkatan Kepercayaan Diri dan Logika Anak SD melalui Sosialisasi di Era Digital - Nugroho, Handi Wilujeng; Hamidi, Kurniawan; Eka Putra, Rama Dani; Fitri, Tessa Zulenia (Journal of Social and Community Service, 2025)
Elementary education plays an important role in shaping children's self-confidence and logical thinking skills, especially in the increasingly complex digital era. However, many children have difficulty in developing these aspects due to the lack of appropriate stimulation. The purpose of this community service activity is to provide socialization and assistance to 6th grade elementary school students in increasing their self-confidence and logical thinking skills. This activity is carried out through interactive methods, exploration-based, and persuasive approaches. This activity involves teachers, as well as educational facilitators in the form of training, educational games, and discussion sessions. The results of the community service show that this approach has a positive impact on children's cognitive and social development. Children who participate in this program experience increased courage in communicating and are better able to solve problems independently. This activity can be an effective model in supporting elementary education in the digital era.